Aplikasi IoT Pada Sistem Monitoring Cairan Infus Berbasis Raspberry PI - Marfin Marfin (STMIK Budi Darma, 2022)
In the medical world, the role of intravenous fluids is very important because it can support the patient's treatment process. However, at this time, the comparison of medical personnel with the number of patients often finds that the installed infusion fluids are not properly monitored by the officers, thus affecting the healing process and satisfaction of patients and their families. On the other hand, rapid technological advances can be used for all fields including medical, therefore the researchers made a smart device that utilizes a photodiode [1] as a sensor to detect intravenous fluids and can provide information to medical staff in real time via smartphone devices. [2]. This device utilizes the Raspberry PI board as a data processor and executor of the data received from the sensor. Raspberry PI itself is a smart device that can process data to data execution because it is equipped with a GPIO pin that can be connected to other external devices [3]. With the design of this device, officers get information on the installed infusion fluids starting from the drip, the discharge to the drip rate. In addition, if the infusion fluid is about to run out, the officer's smartphone will give a notification in the form of vibration and ringing so that the officer can act quickly and precisely